2012
DOI: 10.1177/0734904112446125
|View full text |Cite
|
Sign up to set email alerts
|

Dripping behavior of burning polymers under UL94 vertical test conditions

Abstract: This article studied the dripping behavior of eight polymers under UL94 vertical test conditions. The results suggested two different dripping behaviors: Type I, dripping with uniform- and small-sized drops with the short first dripping time, and Type II, dripping with irregular- and large-sized drops with the long first dripping time. Polymers of Type I dripping had dominant decomposition mechanism of random-chain scission, low activation energy of viscous flow, and high ratio of effective heat of combustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 12 publications
1
61
0
Order By: Relevance
“…As shown in Table 2, the burning time of pure PS was only 15 s. However, with the adding of TPP, the time it took the flame to reach the holding clamp increased, and the UL-94 rating of PS/TPP-S was V-2. During the UL-94 test, we observed that the drops of PS/TPP-S nanocomposite were small, with a short initial drip time, and that the drips speed was faster than that of pure PS, which can take away flame by dripping [35] . As is known to all, TPP is not only a flame retardant but also a plasticizer; it can weaken the intermolecular force of PS, resulting in increased mobility of the polymer chain.…”
Section: Loi and Ul-94 Testsmentioning
confidence: 93%
“…As shown in Table 2, the burning time of pure PS was only 15 s. However, with the adding of TPP, the time it took the flame to reach the holding clamp increased, and the UL-94 rating of PS/TPP-S was V-2. During the UL-94 test, we observed that the drops of PS/TPP-S nanocomposite were small, with a short initial drip time, and that the drips speed was faster than that of pure PS, which can take away flame by dripping [35] . As is known to all, TPP is not only a flame retardant but also a plasticizer; it can weaken the intermolecular force of PS, resulting in increased mobility of the polymer chain.…”
Section: Loi and Ul-94 Testsmentioning
confidence: 93%
“…The droplets become small and first dripping time also decreased due to increasing TPP amount. The droplets of PS/TPP dripped fastly and took away the flame drop by drop [38]. As we know, TPP are not only flame retardants but also plasticizers and can weaken the intermolecular force of polystyrene, which results in increasing the mobility of the polymer chain increased by TPP loading.…”
Section: Loi and Ul-94 Testsmentioning
confidence: 98%
“…Another accepted finding is the dependence of melting/dripping behaviors on the glass transition temperature. Zhang et al, Kandola et al, and Wang et al have found that the lower the glass transition temperature is the higher tendency of melting/dripping the polymer has. The reason should be that thermoplastics easily lose their dimensional stability when their glass transition or melting temperature, respectively, is exceeded.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, the dripping phenomena of several polymers under the UL‐94 vertical test conditions were quantified by measuring the dripping time and the drop mass. For each specimen, the UL‐94 flame is applied for 10 seconds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation